Faktor-Faktor yang Memengaruhi Volume Ekspor Briket Arang di PT Gemati Global Industri - Agandri, Bintang Vedarizky; Mufriantie, Fithri (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Indonesia is a country with a wealth of natural resources. This abundant natural resource if used and utilized properly will be very profitable. Charcoal briquettes are one of the processed products derived from natural resources to increase their added value. Seeing this, PT Gemati Global Industri utilizes charcoal briquettes as the main product for export. This study aims to determine the development of PT Gemati Global Industri's charcoal briquette export volume over a certain period of time, analyzing the influence of the rupiah exchange rate on the US dollar, inflation, the quality of charcoal briquettes and export agents simultaneously or partially on the export volume of charcoal briquettes. This study uses a quantitative descriptive method and uses a multiple linear regression approach using primary data and secondary data within a certain period of time. The results of the study show that the development of PT Gemati Global Industri's charcoal briquette exports tends to be stable with an increase in recent months. The results of this study also show that all variables simultaneously have a significant effect on the export volume of charcoal briquettes of PT Gemati Global Industri. This should be taken into account for the company's export activities to be more profitable or at least still profitable. The rupiah exchange rate against the US dollar and inflation have a significant effect. Export agents have a significant effect on the export volume of charcoal briquettes of PT Gemati Global Industri. Meanwhile, the quality of charcoal briquettes does not have a significant effect on the export volume of charcoal briquettes of PT Gemati Global Industri.